A rare case of hyaline cell-rich atypical chondroid syringoma with divergent differentiation - Smita S Masamatti; C Vijaya; Aparna Narasimha (Wolters Kluwer Medknow Publications, 2018)
Chondroid syringoma (CS) also known as mixed tumor of the skin, is a rare benign adnexal tumor accounting for < 0.098%. Epithelial cells arranged in cords and tubules set in myxoid or chondroid stroma. Differentiation such as osteoid, sebaceous or mature adipocytes can be seen rarely. Hyaline cell rich is a rare variant of CS composed of cells with eosinophilic hyaline cytoplasm and plasmacytoid features. CS can have benign, atypical and malignant variants. The term atypical mixed tumor is recommended for those tumors which have histological features of malignancy such as infiltrative margin, satellite tumor nodules and tumor necrosis but without proven metastasis. Very few case reports of hyaline cellrich benign CS have been reported in the past, but to the best of our knowledge, possibly it is the first case of atypical hyaline cellrich CS of the little finger in a 65 year-old female showing divergent differentiation.